The European Nucleotide Archive in 2019. Issue Volume 48:Issue D1(2020) (13th November 2019) - Amid, Clara; Alako, Blaise T F; Balavenkataraman Kadhirvelu, Vishnukumar; Burdett, Tony; Burgin, Josephine; Fan, Jun; Harrison, Peter W; Holt, Sam; Hussein, Abdulrahman; Ivanov, Eugene; Jayathilaka, Suran; Kay, Simon; et al.
Abstract: The European Nucleotide Archive (ENA,  https://www.ebi.ac.uk/ena ) at the European Molecular Biology Laboratory's European Bioinformatics Institute provides open and freely available data deposition and access services across the spectrum of nucleotide sequence data types. Making the world's public sequencing datasets available to the scientific community, the ENA represents a globally comprehensive nucleotide sequence resource. Here, we outline ENA services and content in 2019 and provide an insight into selected key areas of development in this period.